Approximation of compressions of periodic functions in the space L_p, p < 1 - Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Behavior of the best approximation of function compressions by trigonometric polynomials in L_p, p < 1 is investigated.